2006
DOI: 10.1128/iai.74.1.352-361.2006
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of potD in Streptococcus pneumoniae Polyamine Transport and Pathogenesis

Abstract: Polyamines such as putrescine, spermidine, and cadaverine are small, polycationic molecules that are required for optimal growth in all cells. The intracellular concentrations of these molecules are maintained by de novo synthesis and transport pathways. The human pathogen Streptococcus pneumoniae possesses a putative polyamine transporter (pot) operon that consists of the four pot-specific genes potABCD. The studies presented here examined the involvement of potD in polyamine transport and in pneumococcal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 52 publications
(39 reference statements)
2
79
0
5
Order By: Relevance
“…Although the pneumococcal polyamine transporter has been implicated in both pneumonia and murine septicaemia, its role in nasopharyngeal colonization was unknown (Polissi et al, 1998;Ware et al, 2006). Similar to the cad deletion strain, a potABCD mutant was significantly attenuated in a murine respiratory tract colonization model (Fig.…”
Section: Distribution Of Pneumococcal Polyamine Biosynthesis and Tranmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the pneumococcal polyamine transporter has been implicated in both pneumonia and murine septicaemia, its role in nasopharyngeal colonization was unknown (Polissi et al, 1998;Ware et al, 2006). Similar to the cad deletion strain, a potABCD mutant was significantly attenuated in a murine respiratory tract colonization model (Fig.…”
Section: Distribution Of Pneumococcal Polyamine Biosynthesis and Tranmentioning
confidence: 91%
“…Previous studies from our laboratory have shown that inactivation of potD in a mouse-virulent capsular type 3 strain significantly attenuates the progression of disease in systemic and pulmonary murine models, supporting a role for polyamine uptake in pneumococcal pathogenesis (Ware et al, 2006). We have also shown that polyamines may serve as functional analogues for choline molecules during in vitro growth, and a significant increase in PotD expression is seen when pneumococci are exposed to environmental stress and during murine septicaemia Ware et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…A putative pneumococcal polyamine transporter contains a lipoprotein, PotD, which is surface exposed and accessible to antibodies. PotD has been reported to be involved in virulence in both an animal model of sepsis and pneumonia (24,32). These studies were undertaken to investigate the role of PotD in protective immunity and to assess its potential as a vaccine candidate.…”
Section: Discussionmentioning
confidence: 99%
“…The pneumococcal genomes which have been sequenced contain homologues of known genes encoding enzymes which synthesize polyamines from ornithine and arginine. However, uptake of polyamines from the environment appears to be necessary for full expression of pneumococcal virulence (24,32). PotD is a putative polyamine-binding surface protein, and inhibition of its function with antibodies may alter intracellular polyamine levels to an extent which attenuates virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation